EDUKASI DIGITALISASI DAN ECO ENZYME PRODUCTION UNTUK PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN ORGANIC WASTE - Nurrohman, Rosyid; Anwar, Khairil; Hanifa, Ashylla Febriana; Simanjuntak, Romaria Inriani; Siahaan, Shintia; Della, Andi Dhea Rahda; Ajis, Rabiah Amalia; Irirwanas, Intania Djaima; Haryani, Mita; Khoirunisa, Intan Nabila (An-Nizam, 2025)
This community service program was carried out in Tanjung Batu Village, Berau Regency, East Kalimantan, with the aim of empowering local communities through the digitalization of education and the production of eco-enzyme as an innovation in organic waste management. The participants consisted of approximately 30 people, including housewives, youth groups, and students. The activity was implemented using a participatory and collaborative approach through several stages: program preparation, digital-based education, hands-on practice of eco-enzyme production, mentoring, and evaluation. The results show that eco-enzyme production can be conducted in a simple manner using household organic waste, although several technical challenges were encountered during the fermentation process. The program had a positive impact on the community, particularly in raising environmental awareness, reducing kitchen waste, and fostering active participation in waste management practices. In addition, the use of digital media proved effective in disseminating educational materials, even though direct assistance remained necessary to ensure successful implementation. The program also enhanced students’ capacity, particularly in communication skills, digital literacy, and environmental awareness. Overall, the findings confirm that the synergy between environmental innovation and digital education can serve as an effective strategy for sustainable community empowerment, while also contributing to global sustainable development goals.